The Effect of Lemongrass Plant Extract (Cymbopogon nardus (L.) Rendle) on The Number of Fruit Flies (Bactrosera sp) Catches - Sabrina, Yolanda; Sedijani, Prapti; Ilhamdi, Mohammad Liwa; Artayasa, I Putu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fruit flies (Bactrocera sp.) are important pests of horticultural crops because they can cause serious damage and reduce the selling value of the fruit. This study aims to determine the effect of lemongrass (Cymbopogon nardus) plant extract on the number of fruit fly catches and to determine the most effective concentration as a natural attractant. The study was conducted experimentally in a crystal guava plantation in Dasan Tapen Village, West Lombok, using a Randomized Block Design (RBD) with five treatments of lemongrass extract concentrations (0% - 60%) and three replications. Data were analyzed using one-way ANOVA and continued with the LSD test. The results showed that there were four species of fruit flies caught, namely Bactrocera dorsalis, B. carambolae, B. cucurbitae, and B. papayae, with a total of 671 individuals. The 60% concentration produced the highest number of catches (an average of 69), while the control without attractant did not produce any catches. Statistical analysis showed a significant effect between treatments (p < 0.05). It can be concluded that lemongrass ethanol extract has a significant effect on the number of fruit fly catches, and the highest concentration in this study (60%) is more effective than the concentration below it. The concentration of 60% has the highest capture compared to the concentration below it. The use of lemongrass as a natural attractant has the potential as an alternative to environmentally friendly pest control in an integrated agricultural system.